2020
DOI: 10.1001/jamanetworkopen.2020.11335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Symptoms and Fecal Viral Shedding in Patients With Coronavirus Disease 2019

Abstract: IMPORTANCE Coronavirus disease 2019 (COVID-19) is a global pandemic and can involve the gastrointestinal (GI) tract, including symptoms like diarrhea and shedding of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in feces. OBJECTIVE To provide a pooled estimate of GI symptoms, liver enzyme levels outside reference ranges, and fecal tests positive for SARS-CoV-2 among patients with COVID-19. DATA SOURCES An electronic literature search was performed for published (using MEDLINE/ PubMed and Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
341
4
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(387 citation statements)
references
References 48 publications
12
341
4
30
Order By: Relevance
“…In a clinical study involving 651 patients with COVID-19, 74 (11.4%) had at least one gastrointestinal symptom (nausea, vomiting, or diarrhea). 30 A meta-analysis by Parasa et al 2 showed that approximately 12% of 4805 patients with COVID-19 presented gastrointestinal symptoms, including diarrhea (4.3–12.2%), nausea, or vomiting (2.6–8.0%). Furthermore, in a group of 204 COVID-19 patients in China, the rate of diarrhea reached to 34.0%.…”
Section: Covid-19 and Gastrointestinal Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study involving 651 patients with COVID-19, 74 (11.4%) had at least one gastrointestinal symptom (nausea, vomiting, or diarrhea). 30 A meta-analysis by Parasa et al 2 showed that approximately 12% of 4805 patients with COVID-19 presented gastrointestinal symptoms, including diarrhea (4.3–12.2%), nausea, or vomiting (2.6–8.0%). Furthermore, in a group of 204 COVID-19 patients in China, the rate of diarrhea reached to 34.0%.…”
Section: Covid-19 and Gastrointestinal Clinical Featuresmentioning
confidence: 99%
“…1 Besides common respiratory symptoms, some COVID-19 patients experience gastrointestinal symptoms such as diarrhea, nausea, and vomiting. 2 Anal swab specimens from COVID-19 patients tested positive for SARS-CoV-2 nucleic acid and SARS-CoV-2 could be isolated from the stool samples of COVID-19 patients, 3 , 4 indicating the possibility of fecal–oral transmission. Furthermore, an elevated liver function is common in patients with COVID-19, with more significant increases in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) elevations in severe COVID-19 than in mild/moderate COVID-19.…”
Section: Introductionmentioning
confidence: 97%
“…As of July 2020, more than 10 million confirmed cases of Coronavirus Disease (COVID-19) across five continents and over 500 thousand deaths have been reported ( 3 ). While respiratory symptoms are the main presentation of COVID-19, such as dry cough and dyspnea gastrointestinal manifestations have also been reported ( 4 , 5 ). As the number of cases has increased, so too has our knowledge grown about various symptoms associated with the SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al in 2005 demonstrated that SARS-CoV was not only present in stool samples collected from patients, but also in the wastewater of two hospitals [16]. In review of this data, with inclusion of SARS-CoV-2, a meta-analysis by Parasa et al found that 40% of patients with positive RT-PCR for SARS-CoV-2 from nasopharyngeal swabs or respiratory secretions were also found to be positive from stool samples [17]. This data was supported by two recent studies documenting positive SARS-CoV-2 fecal samples from "recovered" COVID-19 patients with negative nasopharyngeal swabs [18,19].…”
Section: Introductionmentioning
confidence: 99%